Nutrient identity modifies the destabilising effects of eutrophication in grasslands - Oliver Carroll; Evan Batzer; Siddharth Bharath; Elizabeth T. Borer; Sofía Campana; Ellen Esch; Yann Hautier; Timothy Ohlert; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Lori Biederman; et al. (Ecology Letters, 2022)
Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On average, N‐based treatments increased mean biomass production by 21–51% but increased its standard deviation by 40–68% and so consistently reduced stability. Adding P increased interannual variability and reduced stability without altering mean biomass, while K+ had no general effects. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony. We show that nutrients can differentially impact the stability of biomass production, with N and P in particular disproportionately increasing its interannual variability.

Species loss due to nutrient addition increases with spatial scale in global grasslands - Eric W. Seabloom; Evan Batzer; Jonathan M. Chase; W. Stanley Harpole; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Isabel C. Barrio; Lori Biederman; Elizabeth H. Boughton; Miguel N. Bugalho; Maria C. Caldeira; et al. (Ecology Letters, 2021)
The effects of altered nutrient supplies and herbivore density on species diversity vary with spatial scale, because coexistence mechanisms are scale dependent. This scale dependence may alter the shape of the species–area relationship (SAR), which can be described by changes in species richness ( S ) as a power function of the sample area ( A ): S = cA z , where c and z are constants. We analysed the effects of experimental manipulations of nutrient supply and herbivore density on species richness across a range of scales (0.01–75 m 2 ) at 30 grasslands in 10 countries. We found that nutrient addition reduced the number of species that could co‐occur locally, indicated by the SAR intercepts (log c ), but did not affect the SAR slopes ( z ). As a result, proportional species loss due to nutrient enrichment was largely unchanged across sampling scales, whereas total species loss increased over threefold across our range of sampling scales.

Grazing affects vegetation diversity and heterogeneity in California vernal pools - Julia Michaels; Evan Batzer; Susan Harrison; Valerie T. Eviner (Ecology, 2021)
Disturbance often increases local‐scale (α) diversity by suppressing dominant competitors. However, widespread disturbances may also reduce biotic heterogeneity (β diversity) by making the identities and abundances of species more similar among patches. Landscape‐scale (γ) diversity may also decline if disturbance‐sensitive species are lost. California’s vernal pool plant communities are species rich, in part because of two scales of β diversity: (1) within pools, as species composition changes with depth (referred to here as vertical β diversity ), and (2) between pools, in response to dispersal limitation and variation in pool attributes (referred to here as horizontal β diversity ). We asked how grazing by livestock, a common management practice, affects vernal pool plant diversity at multiple hierarchical spatial scales. In terms of abundance‐weighted diversity, grazing increased α both within local pool habitat zones and at the whole‐pool scale, as well as γ at the pasture scale without influencing horizontal or vertical β diversity. In terms of species richness, increases in α diversity within habitat zones and within whole pools led to small decreases in horizontal β diversity as species occupancy increased. This had a dampened effect on species richness at the γ (pasture) scale without any loss of disturbance‐sensitive species. We conclude that grazing increases species richness and evenness (α) by reducing competitive dominance, without large disruptions to the critical spatial heterogeneity (β) that generates high landscape‐level diversity (γ).